PENGUKURAN KUALITAS LAYANAN BUKALAPAK.COM TERHADAP KEPUASAN KONSUMEN DENGAN METODE WEBQUAL 4.0 - Fatur Ilham Farlevi; Tata Sutabri (CV. ADIBA AISHA AMIRA, 2023)
This study demonstrates the importance of a high-quality website in e-commerce, as consumers interact with companies through the website. Bukalapak.com is an example of an online buying and selling service provider that has successfully achieved customer satisfaction based on the Webqual 4.0 method, which consists of usability, quality of information, and quality of interaction variables. This research also provides insights into the factors that contribute to customer satisfaction in e-commerce, thereby helping companies that provide online buying and selling services to improve their website quality and enhance customer satisfaction